2019
DOI: 10.1016/j.gore.2018.12.003
|View full text |Cite|
|
Sign up to set email alerts
|

Mucinous adenocarcinoma of the endometrium with metastasis to the clitoral glans after pelvic exenteration for radiation resistant vaginal cuff recurrence

Abstract: Mucinous adenocarcinoma of the endometrium (MACE) is a rare subtype of endometrial adenocarcinoma that often presents a significant diagnostic challenge due to its variation from the conventional morphologic appearance of endometrioid epithelium. This case report is of a woman who has survived 4 years after pelvic exenteration and subsequent vulvectomy for recurrent MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 7 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…However, the extent of IM/diff areas required to increase the aggressiveness of an EC is unknown; in the majority of papers, it was unclear if IM/diff features were focal or diffuse. With the exception of case described by Mogor in which the recurrent tumor exhibited intestinal differentiation, in the remaining cases, including our one, histological evaluation of the metastatic/recurrent tumor was not performed, and for this reason, it is not clear if the intestinal component is more aggressive in comparison to the endometrioid one [13].…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…However, the extent of IM/diff areas required to increase the aggressiveness of an EC is unknown; in the majority of papers, it was unclear if IM/diff features were focal or diffuse. With the exception of case described by Mogor in which the recurrent tumor exhibited intestinal differentiation, in the remaining cases, including our one, histological evaluation of the metastatic/recurrent tumor was not performed, and for this reason, it is not clear if the intestinal component is more aggressive in comparison to the endometrioid one [13].…”
Section: Discussionmentioning
confidence: 75%
“…AEH was detected in the background endometrium of two cases: one a mixed form, while it was unclear if an endometrioid component was present in the second case. In both patients, no IM/diff was found in benign glands [11,13]. Alternative pathogenic mechanisms and precursors beside AEH may be considered for pure forms: the tumor reported by Rubio arose after previous removal of an endometrial polyp with IM/diff, and AEH was not found in the background endometrium [14].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations